Landasan Konseptual Psikologi Pendidikan: Respon terhadap Nilai Lokal Dan Perkembangan Global - Utari, Rr Finandita (Sultan Idris Journal of Psychology and Education, 2024)
This article discusses the importance of philosophy of science in forming a conceptual foundation for educational psychology in Indonesia that is responsive to local values ​​and global developments. The background of this study highlights the need for an educational approach that emphasizes not only cognitive aspects, but also moral, social, and spiritual values ​​in forming a whole individual. The main objective of this paper is to analyze the integration of Western educational psychology theories—such as Piaget, Vygotsky, Bandura—with local wisdom such as mutual cooperation and spirituality in the context of Indonesian education. The method used is a literature study of Western philosophical literature, educational psychology theories, and Indonesian national educational values. The results of the study show that this integration faces challenges such as the dominance of Western individualistic approaches, but also offers great opportunities to build contextual curricula, character education, and holistic approaches. In conclusion, the philosophy of Indonesian educational psychology can develop into an educational system that is not only locally relevant but also globally competitive, by prioritizing a balance between rationality, spirituality, and cultural values.